Health risk assessment on heavy metals in drinking and surface water of communities in bauxite mining areas - Zety Abrar Naim, Mahad; Zailina, Hashim; Norazura, Ismail; Jamal Hisham, Hashim (Community Health Society Malaysia, 2019)
Background: The mining of bauxite ore in Kuantan, Pahang has been going since early 2013. Bauxite ore contains radionuclides and heavy metals by which uncontrolled bauxite mining, can pollute waterways. These can pose great threat to environment and human health. The study objectives were to determine and compare the concentrations of selected heavy metals; aluminium (Al), arsenic (As), cadmium (Cd), chromium (Cr), nickel (Ni) and lead (Pb) in water as well as to evaluate the risk of drinking such water.